Effect of Expressive Writing Intervention on Health Outcomes in Breast Cancer Patients: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. - Chunlan Zhou; Yanni Wu; Shengli An; Xiaojin Li (PLoS ONE, 2015)
Background Numerous randomized controlled trials (RCTs) have arrived at conflicting conclusions on expressive writing (EW) as an intervention for breast cancer (BC) patients, but there has been no meta-analysis of these studies to assess the effectiveness of EW in BC population. Methods PubMed, Web of Science, The Cochrane Library, EMBASE, and CINAHL and the www.clinicaltrial.gov database on ongoing clinical trials were searched to identify all the RCTs investigating efficacy of EW on the physical and psychological health in BC patients. The risk of bias of the original studies was assessed using the Cochrane Collaboration's tool. Our primary outcomes for physical and psychological health were respectively negative somatic symptoms and negative mood which were stratified by emotional, benefit-finding and multiple prompts in sub-group analyses. The data were analyzed using Review Manager 5.2 and Stata version 12.0 statistical software. Results Of the 5,232 titles screened, we identified 11 RCTs with a total of 1,178 participants. The pooled results showed a significant effect of EW using either an emotional prompt or a benefit-finding prompt on reducing negative somatic symptoms in BC patients in the ≤3-month follow-up group [Mean Difference (MD), -13.03, 95% CI, -19.23 to -6.83, P<0.0001; MD, -9.18, 95% CI, -15.57 to -2.79, P = 0.005]. There was no significant effect of EW on physical health in the >3-month follow-up group. There were no significant differences regarding psychological health indexes between EW intervention and control groups at any of the follow-up time-points (P>0.05). Conclusion This systematic review and meta-analysis reveals that EW intervention may have a significantly positive impact on the physical health but not the psychological health in BC patients, but this benefit may not last long. However, further high-quality studies with more homogeneity are needed to confirm the current findings.